Komunikasi Antarpribadi Orang Tua Dan Anak Tentang Kebencanaan Di Aceh - Irma, Ade; Mubarak, Ahmad Yusuf (JAROW: Journal of Ar-Raniry on Social Work, 2024)
Aceh is a province that is prone to disasters, not only natural, but also non-natural and social disasters. Disasters that occur always leave sadness, harm toward many people, and even take a large number of lives. The 2004 Tsunami disaster in Aceh taught many people to remain alert, so they need to equip themselves with knowledge about disasters. Understanding disaster issues can be learned and must begin through interpersonal communication between parents and children at home. The way to obtain data related to forms of interpersonal communication between parents and children about disasters is to use qualitative methods. This method is used to be able to dig up detailed information. The technique for determining informants is carried out purposively. Answers from informants are obtained by interviewing the target in depth. From the interview results, it was found that forms of interpersonal communication between parents and children about disasters can be done in 4 (four) ways, those are, 1) providing education and understanding of children about disaster issues, 2) communicating disaster issues to children openly, 3) providing support for children to deepen their knowledge of disasters, and 4) instill a caring attitude in children towards others.